Effect of animal species and supplementary feeding on digestion and energy utilization by sheep and goats grazing arid-area rangelands - Askar A.R.; Salama R.; El-Shaer H.M.; Raef O. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Fifty-two non-productive females, 26 Balady goats and 26 Abu-duleik sheep, were employed in a 2.5-month experiment to study the effects of animal species and supplementation level on intake, digestion and energy utilization. Animals of each species were divided into two treatments. They all were grazing arid-area rangelands with a limited amount of concentrate supplement, low (1% BW) or high (2% BW). Total energy expenditure (EE) was estimated by heart rate monitors for 48h after individual calibration by oxygen consumption with a face mask open-circuit respiratory system. Acid insoluble ash (AIA), as an internal marker, was used to estimate the individual intake and digestibility for 6 animals per treatment, while bags were used for total fecal collection. Increasing the concentrate supplement level had negative effects on forage intake and digestibility of grazing goats, while the contrary was observed in sheep. The reduction in goat’s digestibility was mainly attributed to the reduction in fiber fraction digestibility. However, grazing sheep supplemented with a high concentrate level consumed more forage and had a higher digestibility, including fiber fraction digestibility. Total EE was similar between animal species at a low supplementation level and significantly increased with a high level in sheep, but not in goats. Energy balance (EB) was negative and similar between animal species at a low supplementation level, while sheep reported positive and better EB than goats with a high level. In conclusion, supplementary feeding is essential to maintain the animals without deterioration while grazing arid-area rangelands but its effects varied between sheep and goats when supplied at a high level (2% BW).
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)